User interface of MUDR electronic health record - Hanzlicek, Petr; Spidlen, Josef; Heroutova, Helena; Nagy, Miroslav (International journal of medical informatics, 2005)
Development of the electronic health record architecture at the EuroMISE Center was inspired by existing European standards and several European projects. The developed EHR named MUDR implements a 3-layer architecture, using XML for communication between application layer and clients. A decision support module implementing the "1999 WHO/ISH Guidelines for the Management of Hypertension" is part of an application layer. Universal graph structure is used both to represent the set of medical concepts in the EHR and to represent the collected data. Advanced methods of interaction between EHR and its user are studied, software prototypes of client applications are developed and their effectiveness evaluated.
Keywords: Decision Support Techniques; chorobopisy - počítačové systémy; User-Computer Interface; metody pro podporu rozhodování; Medical Records Systems, Computerized; Czech Republic; uživatelské rozhraní počítače; Česká republika